Invisible Compromises: Global Business, Local Ecosystems, and the Commercial Bumble Bee Trade. (December 2015) - Reade, Carol; Thorp, Robbin; Goka, Koichi; Wasbauer, Marius; McKenna, Mark
The purpose of this article is to challenge organizational scholars, management educators, and business leaders to consider more deeply the impact of global business activities on local ecosystems. Drawing on the management, sustainability, and entomology literature, we illustrate the complex relationship between global business and biodiversity loss through the lens of the commercial bumble bee trade. Global firms in this trade rear and supply bees for greenhouse crop pollination. We build on a well-known global strategy framework used in management education by adding a sustainability dimension, and offering propositions for the relationship between global business strategy and the strength of environmental sustainability. We conclude that a locally responsive, place-sensitive business strategy supports the strongest degree of environmental sustainability, and addresses the invisible compromises to ecosystem health that may result from the efforts of global firms to provide otherwise beneficial products and services.